1988
DOI: 10.1111/j.1432-1033.1988.tb14105.x
|View full text |Cite
|
Sign up to set email alerts
|

The protection by ascorbate and glutathione against microsomal lipid peroxidation is dependent on vitamin E

Abstract: Lipid peroxidation of rat liver microsomal fractions was monitored by its low-level cheniiluniinescence in preparations from controls and vitamin-E-deficient animals. Measurements were made (a) of the duration of the lag phase T~ after initiation with NADPH/iron-ADP and (b) of the slope of the chemiluminescence increase.In microsomes with normal vitamin E (a-tocopherol) level the lag phase T,, was substantially increased by ascorbate; in contrast, even an enhanced peroxidation was observed with ascorbate in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
102
0
3

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 334 publications
(111 citation statements)
references
References 28 publications
6
102
0
3
Order By: Relevance
“…The ascorbate-glutathione cycle was implicated in the reduction of the tocopheroxyl radical to tocopherol (Fryer, 1992). In vitro experiments showed that the tocopherol mediated protection against lipid peroxidation is strongly enhanced by the presence of ascorbate and glutathione (Leung et al, 1981;Niki et al, 1984;Liebler et al, 1986;Wefers and Sies, 1988). Furthermore, ascorbate and glutathione were found to act in concert to keep tocopherol in the reduced, active state in membranes isolated from human platelets and erythrocytes (Chan et al, 1991;Constantinescu et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ascorbate-glutathione cycle was implicated in the reduction of the tocopheroxyl radical to tocopherol (Fryer, 1992). In vitro experiments showed that the tocopherol mediated protection against lipid peroxidation is strongly enhanced by the presence of ascorbate and glutathione (Leung et al, 1981;Niki et al, 1984;Liebler et al, 1986;Wefers and Sies, 1988). Furthermore, ascorbate and glutathione were found to act in concert to keep tocopherol in the reduced, active state in membranes isolated from human platelets and erythrocytes (Chan et al, 1991;Constantinescu et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that growth, chlorophyll, and carotenoid content as well as photosynthetic FPSII are reduced in vte1cad2 as compared to the parental lines suggests that the presence of at least one of the two antioxidants, tocopherol or glutathione, is required to sustain normal photosynthetic efficiency. Previously, it was suggested that oxidized tocopherol is reduced via the ascorbate-glutathione cycle (Leung et al, 1981;Niki et al, 1984;Liebler et al, 1986;Wefers and Sies, 1988). Although the exact mechanism is unclear, the simultaneous deficiency in tocopherol and glutathione might result in an accumulation of reactive oxygen species, finally leading to a degradation of chlorophyll and a decrease in photosynthetic quantum yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of ␣-tocopherol to maintain a steady-state rate of peroxyl radical reduction in the plasma membrane depends on the recycling of ␣-tocopherol by external reducing agents such as ascorbate or thiols (20). In this way, ␣-tocopherol is able to function again as a free radical chain-breaking antioxidant, even though its concentration is low (21).…”
Section: Reactive Oxygen Species and Sperm Physiologymentioning
confidence: 99%
“…Interestingly, callose formation was strongly correlated with aluminuminduced oxidative damage to membrane lipids and changes in intracellular calcium homeostasis, suggesting a mechanistic link between lipid peroxidation and callose synthesis (Jones et al, 1998;Yamamoto et al, 2001). Because tocopherols are proposed to function effectively in the scavenging of lipid peroxy radicals responsible for the propagation of polyunsaturated fatty acid oxidation (Wefers and Sies, 1988;McKersie et al, 1990;Fryer, 1992;Munné-Bosch and Alegre, 2002), it is tempting to speculate that tocopherol deficiency may indirectly affect callose synthesis by increasing the extent of lipid peroxidation in the chloroplast membranes. Apparently consistent with this view, it has recently been postulated that tocopherols play a role in intracellular signaling by controlling accumulation of lipid hydroperoxides, which are derived from lipid peroxidation and used for JA biosynthesis (Schaller, 2001;Munné-Bosch and Alegre, 2002;Munné-Bosch and Falk, 2004).…”
Section: Callose Deposition In the Vascular Tissue Correlates With Tomentioning
confidence: 99%